HABITAÇÃO SOCIAL EM PRESIDENTE PRUDENTE-SP - Sibila Corral de Arêa Leão Honda (Universidade do Oeste Paulista, 2010)
Presidente Prudente, historically, has a great sociospatial segregation. The municipality has not shown an inclusive policy nor public policies for the definition of Special Zones of Social Interest or the construction of social housing. However, there are many housing projects of social interest deployed in the city. Some of these projects were funded by institutions outside the government, like The Rotary Foundation. The analysis of its insertion in the urban net, urban deployment, as well as its architectural design is very important to identify their suitability for the beneficiary population. Thus, the objective of this research was to analyse one of those implemented housing projects, and several surveys were executed to support the findings of postoccupation.